Empowering Women Fishpond in Developing the Home Business of the Milk Fish Crackers Industry - Tranggono, Didiek; Budiwitjaksono, Gideon Setyo; Pratiwi, Yunita Satya (Journal of Business Social and Technology, 2024)
The development of milkfish farming in traditional ponds must of course be based on the potential possessed. One of the most important potentials is the local knowledge of the community about the cultivation system in ponds. The Program for the Application of Research Results for the Community (PIHAT), is directed to provide knowledge and insight to group partners related to the development of milkfish cracker products by improving packaging design, adding shrimp cracker products, and payus fish crackers, as well as marketing management including online marketing, so that a suitable marketing network development model can be obtained and smooth productivity and sales. Meanwhile, the target of the PIHAT Program is the development of milkfish cracker business as an additional source of income for fishing families in Kalanganyar Village, so that more comprehensive knowledge can be achieved on how to increase milkfish cracker production including how to market effectively and efficiently. This series of activities is in addition to identifying partner problems, finding solutions, monitoring, and packaging of milkfish cracker products in supporting marketing; The output of activities is websites, catalogs, scientific articles in accredited national journals, increasing knowledge, improving product quality, improving packaging quality, and improving marketing management. The results achieved in this service activity are that KUB Planet Bandeng which is an average fisherwoman has improved in quality both in terms of taste, packaging, and marketing network.